Up to Four Distinct Polypeptides Are Produced from the γ34.5 Open Reading Frame of Herpes Simplex Virus 2 - Korom, Maria (American Society for Microbiology, 2014)
The herpes simplex virus 1 (HSV-1) ICP34.5 protein strongly influences neurovirulence and regulates several cellular antiviral responses. Despite the clinical importance of HSV-2, relatively little is known about its ICP34.5 ortholog. We found that HSV-2 produces up to four distinct forms of ICP34.5 in infected cells: a full-length protein, one shorter form sharing the N terminus, and two shorter forms sharing the C terminus. These forms appeared with similar kinetics and accumulated in cells over much of the replication cycle. We confirmed that the N-terminal form is translated from the primary unspliced transcript to a stop codon within the intron unique to HSV-2 γ34.5. We found that the N-terminal form was produced in a variety of cell types and by 9 of 10 clinical isolates. ICP27 influenced but was not required for expression of the N-terminal form. Western blotting and reverse transcription-PCR indicated the C-terminal forms did not contain the N terminus and were not products of alternative splicing or internal transcript initiation. Expression plasmids encoding methionine at amino acids 56 and 70 generated products that comigrated in SDS-PAGE with the C1 and C2 forms, respectively, and mutation of these sites abolished C1 and C2. Using a recombinant HSV-2 encoding hemagglutinin (HA)-tagged ICP34.5, we demonstrated that the C-terminal forms were also produced during infection of many human and mouse cell types but were not detectable in mouse primary neurons. The protein diversity generated from the HSV-2 γ34.5 open reading frame implies additional layers of cellular regulation through potential independent activities associated with the various forms of ICP34.5. IMPORTANCE The herpes simplex virus 1 (HSV-1) protein ICP34.5, encoded by the γ34.5 gene, interferes with several host defense mechanisms by binding cellular proteins that would otherwise stimulate the cell's autophagic, translational-arrest, and type I interferon responses to virus infection. ICP34.5 also plays a crucial role in determining the severity of nervous system infections with HSV-1 and HSV-2. The HSV-2 γ34.5 gene contains an intron not present in HSV-1 γ34.5. A shorter N-terminal form of HSV-2 ICP34.5 can be translated from the unspliced γ34.5 mRNA. Here, we show that two additional forms consisting of the C-terminal portion of ICP34.5 are generated in infected cells. Production of these N- and C-terminal forms is highly conserved among HSV-2 strains, including many clinical isolates, and they are broadly expressed in several cell types, but not mouse primary neurons. Multiple ICP34.5 polypeptides add additional complexity to potential functional interactions influencing HSV-2 neurovirulence.